Digital art and meaning : reading kinetic poetry, text machines, mapping art, and interactive installations - Simanowski, Roberto (Electronic mediations, 2011)
In a world increasingly dominated by the digital, the critical response to digital art generally ranges from hype to counter hype. Popular writing about specific artworks seldom goes beyond promoting a given piece and explaining how it operates, while scholars and critics remain unsure about how to interpret and evaluate them. This book aims to demonstrate how such critical work can be done, offering close readings of varied examples from genres of digital art such as kinetic concrete poetry, computer-generated text, interactive installation, mapping art, and information sculpture.